Development of nano - Eren, Sezin. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2023., 2023)
Recent developments in nano/micromotor based smart drug delivery and diag nosis systems have gained much attention due to their efficient capabilities and unique features. Smart drug delivery systems are preferred for reduced side effects, increased effectiveness, and controlled release in specific locations. Nano/micromotors enable motion control and propulsion, leading to reduced drug concentration, faster delivery, and enhanced penetration into inaccessible tissues. Hence, in the first part of the the sis, self-functionalized polymer poly(3-aminophenylboronic acid) (PAPBA) enriched nanomotors were developed by conjugating Paclitaxel (PTX) to PAPBA/platinum (Pt )-nickel (Ni) / Pt according to demonstrate their efficacy in smart drug delivery with catalytic propulsion. Controlled drug delivery was achieved by inducing N ear-Infrared irradiation (NIR) and altering the pH. Drug release and interaction of PAPBA-enriched nanomotors loaded with drugs were studied using M CF-7 breast can cer cells. In the second study of the thesis, two segmented, gold (Au), iron-nickel (Fe - Ni) as metallic micromotors were synthesized according to carry out controlled release of anti-cancer drug doxorubicin (DOX) to breast cancer cells and diagnosis of breast cancer with mag netic propulsion. Au segment surface of electrochemical fabricated micromotors were engineered to provide drug (DOX) loading and antibody (antiHER2) immobilization as capturing agent. Engineered Au segment surface made possible controlled drug release in acidic cancerous environment. Magnetic (Fe-Ni) segment ensured controlled drug delivery to MCF-7. Spheroids with nano/ micromotor drug delivery systems offer valu able insights for optimizing their clinical use. These approaches highlight the potential of nano/micromotors as smart drug delivery methods over conventional systems. NOTE Keywords : Nanomotor, micromotor, Drug Delivery, Drug release, Spheroid, Anti HER2, PAPBA, Paclitaxel, Doxorubicin, MCF-7 Cells.
Keywords: Cancer -- Diagnosis.; Nanostructured materials.